Effects of transionospheric signal decorrelation on Global Navigation Satellite Systems (GNSS) performance studied from irregularity dynamics around the northern crest of the EIA - Das, T.; Roy, B.; Paul, A. (Radio science, 2014)
Transionospheric satellite navigation links operate primarily at L band and are frequently subject to severe degradation of performances arising out of ionospheric irregularities. Various characteristic features of equatorial ionospheric irregularity bubbles like the drift velocity, characteristic velocity, decorrelation time, and decorrelation distance can be determined using spaced aerial measurements at VHF. These parameters measured at VHF from a station Calcutta situated near the northern crest of the Equatorial Ionization Anomaly (EIA) in the geophysically sensitive Indian longitude sector have been correlated with L band scintillation indices and GPS position accuracy parameters for identifying possible proxies to L band scintillations. Good correspondences have been observed between decorrelation times and distances at VHF with GPS S4 and Position Dilution of Precision during periods of GPS scintillations (S4 > 0.3) for February–April 2011, August–October 2011, and February–April 2012. A functional relation has been developed between irregularity drift velocity measured at VHF and S4 at L band during February–April 2011, and validation of measured S4 and predicted values performed during August–October 2011 and February–April 2012. Significant improvement in L band scintillation prediction and consequent navigational accuracy will result using such relations derived from VHF irregularity measurements which are much simpler and inexpensive. Key Points Irregularity dynamical information derived from VHF spaced aerial measurementsProxy indicators of GNSS performance degradationPrediction of GPS L band S4